Uji Aktivitas Antibakteri Ekstrak Serbuk Gergaji Kayu Eboni (Diospyros celebicaBakh.) Terhadap Bakteri Staphylococcus aureus dan Escherichia coli - Wahyuni Wahyuni; Nurlina Ibrahim; Arsa Wahyu Nugrahani (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Ebony (Diospyros celebica Bakh.) is one of the beneficial plants from ebenaceae, especially in traditional medicine. The sawdust extract containing chemical compounds such as tannins, saponins and terpenoids. This research were aimed to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) also to identified the active compounds from sawdust extracts of D. celebica Bakh. against Staphylococcus aureus and Escherichia coli. The Research methods include extraction using maceration method by ethanol 96%. MIC and MBC determination using dilution and diffusion methods. The Results showed that MIC value of S.aureus and E. coli were 6% and 7%, respectively. While MBC value of S. aureus and E. coli were 12% and 13%, respectively. Identification of chemical compounds were determined by Thin Layer Chromatography (TLC) bioautography method by 10% H2SO4 and anisaldehid-sulfuric acid reagent spray. There were two chemichal compounds that produced, saponin and terpenoid.